Essays on the Christian worldview and others political, literary, and philosophical - Schatkin, Andrew J. (Lanham, Md. : Hamilton Books, 2011)
This collection of essays and thoughts covers such areas as basic Christian thought, which includes traditional family morality and a great concern for alleviating poverty and promoting social justice, political thought comparing the need for a system which includes both socialist and capitalist elements, and the need for values in our society, which has come to emphasize money, power, and greed as philosophical goals and values, though they are not. The book also has thoughts concerning literature, a consideration of what constitutes true progress, the denial in our society of any absolute moral truth, and the substitution of moral relativism as a mistaken ethical system. --publisher description
Thoughts on a few significant topics -- The Christian worldview -- Essays on politics and law -- Literary and philosophical essays.
Includes index.
Description based on print version record.
Keywords: Christian philosophy; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books